SECULAR STATE AND RELIGIOUS NEUTRALITY - Mitrović, Petar (Pravni zapisi, 2022)
In the present paper, the autor provides a critical appraisal of Marko Božić’s understanding of the principle of state secularity, defended in the previous issues of this journal. Firstly, the author critically examines the non-contestability thesis that is arguably held by Božić and argues that it raises the objection of conceptual imperialism. In the following sections, the author turns to Božić’s extralegal theory (and concept) of secularity based upon the notion of “equality in freedoms”. In particular, the author argues: (a) that the concept of secularity that Božić develops is inherently flawed in several important ways; (b) that an extralegal theory of secularity – that of Božić or anyone else – should not be considered a starting point when interpreting a constitutional principle of secularity; (c) that the concept of secularity that Božić develops is by no means a useful interpretative tool in virtue of the fact that it significantly departs from positive law.